Antenna competition to boost Active Interference Cancellation in cognitive MIMO-OFDM - Schmidt, J.F.; R. López-Valcarce (IEEE Sensor Array and Multichannel Signal Processing Workshop (SAM), 2014)
Active Interference Cancellation (AIC) techniques for OFDM spectrum sculpting have gained interest over the last years, and several extensions to the MIMO case have been recently proposed. However, these designs do not fully exploit the spatial diversity provided by the multiple transmit antennas, as canceler allocation is fixed. This paper proposes a more general mechanism for the allocation of the cancellation subcarriers across antennas in order to better exploit spatial diversity. In particular, we present a novel AIC design for cognitive MIMOOFDM systems, in which transmit antennas compete against each other for a fixed number of cancellation subcarriers. We show that this more general allocation approach results in significant performance improvements with respect to previous designs.
Keywords: cognitive radio; dynacs; spectrum shaping